Antizyme inhibitor 2 (AZIN2) associates with better prognosis of head and neck minor salivary gland adenoid cystic carcinoma. Issue 8 (25th June 2021) - Hämetoja, Hanna; Andersson, Leif C.; Mäkitie, Antti; Bäck, Leif; Hagström, Jaana; Haglund, Caj
Abstract : The key regulator of the polyamine biosynthetic pathway is ornithine decarboxylase (ODC). ODC is activated by antizyme inhibitor 1 (AZIN1) and 2 (AZIN2). AZIN1 and recently AZIN2 have been related to cancer; however, their functions in adenoid cystic carcinoma (ACC) have not been studied. We performed immunohistochemical study on minor salivary and mucous gland ACC tissue samples of patients treated at the Helsinki University Hospital (Helsinki, Finland) during 1974–2012. We scored AZIN1 and 2 immunoexpression in 42 and 45 tumor tissue samples, respectively, and correlated them with clinicopathological factors and survival. Enhanced AZIN2 expression was associated with better survival. In addition, both AZINs were seen more commonly in cribriform and tubular than in solid growth patterns. AZIN1 expression did not correlate with the studied clinicopathological factors. It seems that AZIN2 expression is higher in cancer tissue with secretory functions. In ACC tissue, high AZIN2 expression could be related to well‐differentiated histological type which still has a functioning vesicle transportation system. Thus, AZIN2 could be a prognostic factor for better survival of ACC patients.